JEWELRY DESIGN DEVELOPMENT BASED ON CHINESE PERANAKAN CULTURE IN INDONESIA USING RICE STRAW AS MATERIAL - Caitlyn
Indonesia, as the fourth largest producer of rice, also produces plenty of rice straw, around 50 million tons each year. Rice straw is the number one waste from Indonesia farms and agricultural industry. As of now, parts of the usage of rice straw is nothing more than farm feed and compost, while the rest is getting burned back in the field. There’s a big potential of developing a product from the rice straw due to its durable and flexible characteristic of the straw itself. This research’s end product is a collection of jewellery made out of rice straw based on the cultural reference of Chinese Peranakan that resides in Indonesia. The culture itself holds many symbolism and life philosophy that makes an interesting narrative for the design of the jewellery. The current rise of the Chinese Peranakan culture since the 60s until early 2000s is one of the reasons this culture is chosen to be the base of the design. The production of this research can create new skill sets and businesses. The final product of this research is a collection of earrings, and necklaces that is made out of rice straw using the method of weaving, mashing the fibres together, and colouring. The intention of this research is to develop a product that has value from a material that is considered as waste.